Potensi Wisata Kuliner Untuk Pengembangan Pariwisata di Kota Medan - Chairiza Azmi (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
Culinary tourism is a part of tourism. The variety of culinary delights available in each region can be developed as an attraction for tourists to visit an area, this phenomenon can also be seen in the city of Medan. The great potential in Medan city has not been supported by adequate information about Medan’s culinary wealth. Many factors cause a lack of information for tourists. Therefore this study aims to: 1). Especially the types and culinary potential typical of Medan, North Sumatra, 2). Avoiding the problems encountered in developing culinary specialties of Medan in supporting tourism potential in the city of Medan. This research uses a type of qualitative research, and descriptive data analysis techniques, which will discuss what potential it has and how to develop it. The results of the study show that there is potential for culinary tourism that can be developed as a tourist attraction in the city of Medan, 1). Culinary tours in the field include rujak kolam, mie aceh titi bobrok, tip top restaurant and ucok durian, 2). The problem that is often faced in the development of culinary tourism in the city of Medan is the lack of promotion and expansion of marketing both through print and electronic media.